PENGARUH ION Pb(II) DAN ION Cd(II) TERHADAP EFEKTIVITAS FOTOREDUKSI ION Hg(II) YANG TERKATALISIS TiO2 - , CORY NOVI; , Prof.Dr. Endang Tri Wahyuni, M.S, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The influences of Pb(II) and Cd(II) ions with variation of concentration and pH on the photoreduction of Hg(II) ion photocatalyzed by TiO2 have been studied. The photoreduction process was carried out by irradiating a mixture of Hg(II) ion solution and TiO2 photocatalyst powder with or without Pb(II) and Cd(II) ions in a closed reactor equipped with UV lamp and under continous stirring. The effectiveness of the photoreduced Hg(II) ion in the solution was calculated by substracting the initial Hg(II) concentration by the unreduced concentration after the photoreduction process. The unreduced Hg(II) ion concentration was determined by Cold Vapor Atomic Absorption Spectrophotometric method (CV-AAS). The results of the research showed the effectiveness of Hg(II) ion photoreduction catalyzed by TiO2 improves with the increasing Pb(II) ion because of sinergy effect in the solution. On the other hand, the effectiveness of Hg(II) ion photoreduction decreases by increasing amount of Cd(II) ion because of competition in adsorption. Increasing pH 1 to 4 in the presence of Pb(II) ion can improve Hg(II) ion photoreduction, meanwhile the addition of Cd(II) ion causes the decrease in the Hg(II) ion photoreduction. When the pH was further increased from 4 to 9, the addition of both metal ions, causes the decrease of Hg(II) ion photoreduction. The presence of both metal ions give no effect on Hg(II) ion photoreduction for solution with pH higher than 9. The crystallinity of TiO2 decreased after it is used as photocatalyst in Hg(II) ion photoreduction in the presence of Pb(II) or Cd(II) ions.